Análise eletromiográfica dos músculos bíceps femoral, reto femoral e vasto lateral durante três variações do exercício de ponte supino - Anelize Cini; Cláudia Silveira Lima (Universidade Estadual do Oeste do Paraná, 2014)
The hamstrings have high rate prevalence and lesion recurrence rate in the sport. Recently, the stability target has been a concept highly studied for its high relationship with this type of injury. In this sense, the objective of the study was to verify the electrical activation of the biceps femoris, vastus lateralis and rectus femoris during supine bridge exercises. The study included four female students with a mean age of 26.5 ± 1.73 years. Muscle participation was analyzed by means of electrical activation of the biceps femoris, vastus lateralis and rectus femoris using electromyography. It was performed ten repetitions for the bridge exercise in bipedal support and single leg in stable base, and for bipedal bridge in unstable base. Maximum voluntary isometric contraction (MVIC) 5s for normalization of the electromyographic signal was used. The electrical activation of the biceps femoris muscle (hip extensor) at the bridge bipedal support was 23.3% MVIC for the single leg bridge of 36.9% MVIC and bridge in unstable base with Swiss ball of 54.3% MVIC. For the extensor muscles of the knee (rectus femoris, vastus lateralis) activation ranged from 2.2 to 4.4% MVIC. The biceps femoris muscle has an important recruitment in supine bridge exercises can this be prescribed for strengthening and rehabilitation of these muscles.